Creating and Working with Rubrics - Aubrey L. Stoughton; Brian E. Myers (EDIS)
AEC-388, a 5-page illustrated fact sheet by Aubrey L. Stoughton and Brian E. Myers, describes types of rubrics and how to create them for teachers to evaluate student performance. Published by the UF Department of Agricultural Education and Communication, May 2008.